2014
DOI: 10.1074/jbc.m114.595850
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Monoacylglycerol Acyltransferase 1 Ameliorates Hepatic Metabolic Abnormalities but Not Inflammation and Injury in Mice

Abstract: Background: Mogat1 inhibition improves glucose metabolism in obese mice, but its effects on liver injury are unknown. Results: Mogat1 knockdown improved hepatic metabolic abnormalities but did not reduce liver inflammation or injury. Conclusion: Hepatic injury and metabolic abnormalities are separable disease entities. Significance: Attention to liver injury markers should be made when evaluating metabolic therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
51
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 45 publications
6
51
1
Order By: Relevance
“…As previously reported, the expression of Mogat1 in the lean mouse liver is low, but increases in association with TAG accumulation, similar to that observed for PPARγ (Hall, et al 2014; Lee et al 2012; Soufi, et al 2014; Yu, et al 2016), as we also observed in the current study. In addition hepatic expression of Mogat1, as well as PPARγ, is elevated in humans with NAFLD (Hall et al 2012; Yu et al 2015).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As previously reported, the expression of Mogat1 in the lean mouse liver is low, but increases in association with TAG accumulation, similar to that observed for PPARγ (Hall, et al 2014; Lee et al 2012; Soufi, et al 2014; Yu, et al 2016), as we also observed in the current study. In addition hepatic expression of Mogat1, as well as PPARγ, is elevated in humans with NAFLD (Hall et al 2012; Yu et al 2015).…”
Section: Discussionsupporting
confidence: 92%
“…However, hepatic MOGAT activity has been detected by other laboratories (Hall et al 2012; Yen, et al 2002). Importantly, the increase in Mogat1 expression observed in HF-fed and ob/ob mice is associated with an elevation of hepatic MOGAT activity, which is reduced by Mogat1 ASO ip treatment (Hall et al 2014; Soufi et al 2014). The Mogat1-ASO injections reduced hepatic TAG accumulation in one study (Soufi et al 2014), but not the other (Hall et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, MGAT1 antisense oligonucleotides treatment improved glucose tolerance and hepatic insulin sensitivity (Soufi et al, 2014). We tried to create recombinant hMGAT1 but we could not obtain the membrane fraction which exhibited sufficient MGAT activity.…”
Section: Discussionmentioning
confidence: 99%
“…Since our demonstration of the upregulation of Mogat1 mRNA expression in Agpat2 Ϫ / Ϫ steatotic liver ( 10 ), a few studies using siRNA ( 30 ) or antisense oligonucleotide in an acute setting showed suppression of the expression of Mogat1 in mouse livers ( 31,32 ). This resulted in a modest decrease in the liver TAG and an increase in hepatic insulin signaling and whole body glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%